Pemanfaatan Bahan Ajar Berbasis Blended Learning Pada Siswa SD - Nita Hidayati; Lessa Roesdiana; Betha Nurina Sari (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
The era of the industrial revolution 4.0 is marked by the acceleration of technological development. Nowadays, people are very dependent on technology in carrying out their daily activities. Especially in the learning process known as online learning, this method was applied massively during the covid-19 pandemic. This forces teachers, lecturers and education practitioners to innovate and be creative to develop technology-based teaching materials, which can then be used to achieve learning objectives. However, the facts on the ground show that almost all teachers in schools carry out conventional learning processes and seem boring to students. Based on the problems faced by partners, the solution offered is to accommodate technological developments (e-learning) without having to leave face-to-face learning (face-to-face) here must be an appropriate teaching organization strategy, teaching delivery, and teaching quality, namely by blended learning. The output of the activity is implementing an innovative learning system that is in accordance with current developments, for example blended learning, another outcome is the development of blended learning-based teaching materials that can facilitate students in education. The implementation method is carried out by applying blended learning and compiling teaching materials based on blended learning in order to improve student learning outcomes. Era revolusi industri 4.0 ditandai dengan percepatan perkembangan teknologi. Saat ini, masyarakat sangat tergantung dengan teknologi dalam melakukan aktivitas sehari-hari. Khususnya pada proses pembelajaran dikenal dengan online learning, metode ini diterapkan secara massif selama pandemi covid-19. Hal ini memaksa para guru, dosen dan praktisi pendidikan agar berinovasi dan berkreasi untuk mengembangkan bahan ajar berbasis teknologi, kemudian dapat digunakan untuk mencapai tujuan pembelajaran. Namun fakta dilapangan menunjukkan hampir semua guru di sekolah melaksanakan proses pembelajaran secara konvensional dan terkesan membosankan bagi siswa. Berdasarkan permasalahan yang dihadapi mitra, maka solusi yang ditawarkan adalah mengakomodasi perkembangan teknologi (e-learning) tanpa harus meninggalkan pembelajaran secara tatap muka (face-to-face) haruslah ada strategi pengorganisasian pengajaran, penyampaian pengajaran, dan kualitas pengajaran yang tepat, yaitu dengan blended learning. Luaran dari kegiatan yaitu menerapkan sistem pembelajaran inovatif yang sesuai dengan perkembangan zaman saat ini misalnya blended learning, luaran lainnya adalah dikembangkan bahan ajar berbasis blended learning yang dapat memfasilitasi siswa dalam pendidikan. Metode pelaksanaan yang dilakukan dengan menerapkan blended learning dan menyusun bahan ajar berbasis blended learning agar dapat meningkatkan hasil belajar siswa.